Near-infrared tissue oximetry of beef longissimus muscle for the improvement of meat color and meat color stability - A. Mohan; Terry A. Houser; T.E. Barstow; Melvin C. Hunt (Kansas Agricultural Experiment Station Research Reports, 2009)
Meat color as perceived by consumers serves as a valuable guide for assessing overall quality and wholesomeness of meat. The bright cherry-red color of beef is influenced by tissue oxygen consumption, obstacles to oxygen diffusion, and thickness of the oxymyoglobin layer. The dynamics of meat color depend on several physical properties of muscle including myoglobin redox status and concentration. Physical, chemical, and anatomical differences in muscles cause large variations in color from cut to cut, within a cut, and in cuts made parallel or perpendicular to muscle fibers. Clearly, muscle fiber orientation affects measurements of tenderness and cooking yields; however, variations in myoglobin redox dynamics, oxygen penetration, and color stability due to muscle fiber orientation (parallel or perpendicular) are not well documented. Among the various meat color measurement techniques available, near-infrared (NIR) methods have the advantages of being nondestructive, rapid, inexpensive, and adaptable for online measurements. The NIR tissue oximeter is a relatively new biomedical device that has been used in exercise physiology and in medicine to measure hemoglobin and myoglobin oxygen saturation in brain tissue and cardiac and skeletal muscle. This instrument seems to have promise for use in measuring inherent properties of meat that are related to meat color stability. NIR tissue oximetry may provide continuous real-time measurements of changes in myoglobin oxygen status, thus providing information on tissue oxygenation and hemodynamics. The unique feature of the tissue oximeter is that it uses the theory of photon migration through tissue, allowing for absolute measurement of absorption in, for example, human or animal tissue. If the NIR absorption properties of any chromophore are known, quantitative analysis of color compounds is possible without constant calibration and validation. We are not aware of any research in which NIR tissue oximetry has been used to evaluate color of post-rigor meat. This study was designed to evaluate whether NIR tissue oximetry has promise for measuring meat properties related to meat color. Specific objectives were to determine: (1) effects of parallel vs. perpendicular muscle fiber orientation of meat cuts on NIR measurements, (2) amounts of deoxymyoglobin (DMb), oxymyoglobin (OMb), and total myoglobin (TMb) in the superficial and subsurface layers of beef muscle (longissimus) stored in several packaging formats, and (3) tissue oximeter responses to post-rigor muscle fiber orientation and surface measures of color.
Keywords: Cattlemen& #x27; s Day; 2009; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1010; Kansas Agricultural Experiment Station contribution; no. 09-168-S; Beef; Cattle; Near-infrared(NIR); Meat Color Stability